Characterization of Gene Coding Fusion Protein of Newcastle Disease Virus Infected in Native Chicken in Surabaya - Kirana, Maha; Ernawati, Rahaju; Rahmahani, Jola; Rantam, Fedik Abdul (Jurnal Medik Veteriner, 2022)
This study aimed to discover the homology of nucleotide sequence, homology percentage, and those relations phylogenetic of protein Fusion (F) gene coding of Newcastle disease in domestic chicken (Gallus gallus domesticus) in Surabaya using some comparison isolate from GenBank. Samples were scoured of digestive organs from native chicken, that was collected from a traditional market in Wonokromo, Surabaya. Samples were tested using RT-PCR with primer forward and reverse with target 976bp, a positive sample which is continued with sequencing then homology and nucleotide analysis which is done and which is translated into amino acid. The result of homology chc/SBY/2018 sample has a similarity of 88% with references sequence, while with Lasota vaccine has a similarity of 87%, and the highest result of homology showed by the comparison with various isolates in Indonesia 90-95%. Translation results from nucleotide alignment into amino acid showed shifts in amino acid structure, which is amino acid shifts could be affected by many things like nutrition, wheater, environment, etc. The conclusion was chc/SBY/2018 sample has a quite high similarity with Indonesian isolates and undergoes mutation on nucleotide structure on amino acid and phylogenetic analysis. This study related to some isolates of vaccine and some isolates in Indonesia.